Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Hybridprofile für Trag- und Crashstrukturen - Drossel, Welf-G; Bobbert, Mathias; Böhme, Marcus; Dammann, Christian; Dittes, Axel; Gießmann, Mina; Hühne, Christian; Ihlemann, Jörn; Kießling, Robert; Lampke, Thomas; Lenz, Peter; Mahnken, Rolf; et al. (Intrinsische Hybridverbunde für Leichtbautragstrukturen)

Constitutive modeling of viscoplasticity including phase transformations for graded thermo‐mechanical processing - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Grydin, Olexandr; Schaper, Mirko (PAMM)

Damage simulation of thermo‐chemo‐elasto‐plastic fibre reinforced composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

An uncertainty model for the curing process of transversely fiber reinforced plastics - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

Constitutive modeling of dynamic recrystallization coupled to viscoplasticity - Westermann, Hendrik; Mahnken, Rolf (PAMM)

A deep learning driven uncertain full‐field homogenization method - Henkes, Alexander; Caylak, Ismail; Mahnken, Rolf (PAMM)

A non-equilibrium thermodynamic framework for viscoplasticity incorporating dynamic recrystallization at large strains - Mahnken, Rolf; Westermann, Hendrik (International Journal of Plasticity)

Fuzzy and stochastic approach applied to rubber like materials - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf; Dridger, Alex (Safety and Reliability)

On the Thermodynamics of Dynamic Recrystallization for Viscoplasticity at Large Strains - Westermann, Hendrik; Mahnken, Rolf (14th WCCM-ECCOMAS Congress)